Molecular Docking of Active Compound of Okra (Abelmoschus esculentus L.) on α-Glucosidase as Antidibetic Mellitus Drug Candidate - Nuur'Alimah, Shobiroh; Ambarsari, Laksmi; Farhan, Muhammad (Tropical Biopharmaca Research Center, IPB University, 2026)
Diabetes mellitus (DM) is a leading cause of death among degenerative diseases, primarily due to impaired insulin function that disrupts carbohydrate metabolism. One therapeutic strategy involves α-glucosidase inhibitors that delay glucose absorption. Abelmoschus esculentus (okra) is rich in phenolic and flavonoid compounds with antihyperglycemic and antioxidant activity, suggesting potential as α-glucosidase inhibitors. This study evaluated the inhibitory potential of okra-derived compounds against α-glucosidase using in silico molecular docking with PLANTS and YASARA Structure. The analysis included physicochemical screening, ligand–receptor preparation, and docking simulations, assessing docking score, Gibbs free energy (ΔG), and dissociation constant (Kd). Cannabiscitrin, a flavonoid from okra, demonstrated the strongest binding affinity, outperforming the reference drug acarbose in all parameters. These findings suggest its potential as an alternative antidiabetic agent.